A Pore-Scale Simulation on Thermal-Hydromechanical Coupling Mechanism of Rock. (18th April 2017) - Song, Rui; Cui, Mengmeng; Liu, Jianjun; Ranjith, P. G.; Lei, Yun
Abstract : Thermal-hydromechanical (THM) coupling process is a key issue in geotechnical engineering emphasized by many scholars. Most existing studies are conducted at macroscale or mesoscale. This paper presents a pore-scale THM coupling study of the immiscible two-phase flow in the perfect-plastic rock. Assembled rock matrix and pore space models are reconstructed using micro-CT image. The rock deformation and fluid flow are simulated using ANSYS and CFX software, respectively, in which process the coupled physical parameters will be exchanged by ANSYS multiphysics platform at the end of each iteration. Effects of stress and temperature on the rock porosity, permeability, microstructure, and the displacing mechanism of water flooding process are analyzed and revealed.